2022
DOI: 10.1002/adhm.202102810
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle‐Stabilized Emulsion Bioink for Digital Light Processing Based 3D Bioprinting of Porous Tissue Constructs

Abstract: A challenge for bioprinting tissue constructs is enabling the viability and functionality of encapsulated cells. Rationally designed bioink that can create appropriate biophysical cues shows great promise for overcoming such challenges. Here, a nanoparticle-stabilized emulsion bioink for direct fabrication of porous tissue constructs by digital light processing based 3D bioprinting technology is introduced. The emulsion bioink is integrated by the mixture of aqueous dextran microdroplets and gelatin methacrylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…3D printing of porous hydrogels containing BMSCs would be an ideal route of administration to the target sites for speeding up the bone regeneration. The contact between the structured porous hydrogels and surrounding tissues can significantly promote tissue ingrowth, angiogenesis, and interface fusion [ 24 , 34 ]. Although a number of porous hydrogels have been reported via salt-leaching [ 35 ], organic phases that served as porogens [ 36 ], and cryogelation [ 37 ], which are not ideal to be applied in 3D direct bioprinting of cell-laden porous hydrogels, as it was not possible to encapsulate living cells within polymer solution during the biofabrication process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3D printing of porous hydrogels containing BMSCs would be an ideal route of administration to the target sites for speeding up the bone regeneration. The contact between the structured porous hydrogels and surrounding tissues can significantly promote tissue ingrowth, angiogenesis, and interface fusion [ 24 , 34 ]. Although a number of porous hydrogels have been reported via salt-leaching [ 35 ], organic phases that served as porogens [ 36 ], and cryogelation [ 37 ], which are not ideal to be applied in 3D direct bioprinting of cell-laden porous hydrogels, as it was not possible to encapsulate living cells within polymer solution during the biofabrication process.…”
Section: Discussionmentioning
confidence: 99%
“…The void-forming hydrogels were prepared by DLP-based 3D printing of aqueous emulsion composed of the mixture of dextran solution and GelMA solution with a volume ratio of 1:2 according to our previous study [ 24 ]. Briefly, the dextran and GelMA polymers were dissolved into PBS solution to form 10% (w/v) dextran solution (average Mw ​= ​500, 000; without modification) and 15% (w/v) GelMA solution at room temperature, separately.…”
Section: Methodsmentioning
confidence: 99%
“…Copyright 2020, Elsevier. ( E ) Schematic illustration of DLP-based bioprinting of porous tissue constructs using nanoparticle-stabilized emulsion bioink [ 39 ]. Copyright 2022, Wiley.…”
Section: Materials For 3d Bioprintingmentioning
confidence: 99%
“…The data also showed that the existence of IL-4 and MSCs promoted the differentiation of the M2 phenotype of macrophages, indicating that biological ink has a potential anti-inflammatory function. Tao et al [ 39 ] produced bio-inks through the integration of GelMA solution and β-lactoglobulin (β-LG) nanoparticles/dextran solution mixture and printed tissue constructs using 3D bioprinting technology based on digital light processing ( Figure 1 E). After the ink is solidified, it is immersed in the culture medium to wash out the dextran so as to form pores in situ, allowing nutrients and oxygen to diffuse into the 3D-printed hydrogel construction.…”
Section: Materials For 3d Bioprintingmentioning
confidence: 99%
“…Cell culture and tissue engineering. Hydrogels have been extensively used as scaffolds for cell culture, [186][187][188][189][190] due to the high water content, permeability to oxygen, nutrients and metabolites, and the capability of chemical functionalization of hydrogels to recapitulate in vivo biochemical and biophysical cues. 105,157 The utilization of NCGs for cell culture offers the ability to mimic the filamentous structure of the natural extracellular matrix.…”
Section: Biological Applications Of Ncgsmentioning
confidence: 99%